Neurosyphilis with normal pressure hydrocephalus and dementia paralytica: serial clinical, laboratory and radiological correlations in the 21st century - Kamille Abdool; Karan Seegobin; Kanterpersad Ramcharan; Adrian Alexander; Leandra Julien-Legen; Stanley Lawrence Giddings; Samuel Aboh; Fidel Rampersad (MDPI AG, 2016)
We report a case of a 46-year-old man presenting with a progressive cognitive decline, ataxic gait, urinary incontinence for 4 months and neuroimaging consistent with normal pressure hydrocephalus. The atypical presentation of a progressively worsening dysphasia and a right hemiparesis dismissed as a vascular event 1 month earlier associated with normal pressure hydrocephalus prompted further investigations confirming neurosyphilis also manifesting as dementia paralytica. Treatment using consensus guidelines led to resumption of activities of daily living. Neurosyphilis, considered rare in the neuroimaging era, must still be considered a reversible cause of dementia and other neurological manifestations in contemporary neurological practice.